Constructing Crystalline g‐C3N4/g‐C3N4−xSx Isotype Heterostructure for Efficient Photocatalytic and Piezocatalytic Performances. Issue 2 (30th March 2022) - Xu, Tingting; Xia, Zhonghui; Li, Hongguan; Niu, Ping; Wang, Shulan; Li, Li
Abstract : Graphitic carbon nitride (g‐C3 N4 ) is viewed as a promising visible‐light photocatalyst for industrialization due to its low processing temperature and high chemical stability. However, serious charge recombination caused by incomplete polymerization during direct calcination of nitrogen‐rich precursors significantly limits its photocatalytic performances. To boost charge separation, herein, we propose a rational strategy by constructing a crystalline g‐C3 N4 /g‐C3 N4−x Sx isotype heterostructure through the molten salt method. Theoretical calculation reveals that apparent charge‐transfer channels are formed between g‐C3 N4 and S‐doped g‐C3 N4 layers in the heterostructure. Owing to high crystallinity for decreasing charge recombination and isotype heterostructure for efficient charge transfer, the as‐prepared g‐C3 N4 /g‐C3 N4−x Sx showed remarkable photocatalytic performances with the hydrogen production rate elevated by up to 12.3 times of its singular components. Another novelty of this work is we investigated for the first time the piezocatalytic activity of crystalline g‐C3 N4 by characterizing its performance for H2 O2 generation and KMnO4 reduction. Strikingly, its superior piezocatalytic performance over components can be further improved by NaBH4 treatment, which is uncovered to enhance the asymmetric structure of crystalline g‐C3 N4 by introducing extra cyano groups and removing partial NHx species in its tri‐s‐triazine layer structure. This work opens up new strategies for the design of highly efficient polymeric photocatalysts and highlights the piezocatalytic studies of g‐C3 N4 . Abstract : High cyrstalline g‐C3 N4 /g‐C3 N4−x Sx isotype heterostructure constructed in molten salt showed remarkable photocatalytic and piezocatalytic activity. This is the first report about the investigation of piezocatalytic activities of crystalline g‐C3 N4 .